A comparative assessment of digital platform worker protection in the EU and ASEAN - Nur, Muhammad; Asmorojati, Anom Wahyu; Megawati, Megawati; Zuliyah, Siti; Isdiyanto, Ilham Yuli (Legality : Jurnal Ilmiah Hukum, 2023)
The rapid rise of the digital platform economy, connecting workers with employers, has transformed labor markets globally. This paper explores the regulatory approaches and policies safeguarding digital platform workers in the European Union (EU) and the Association of Southeast Asian Nations (ASEAN). While the EU demonstrates comprehensive labor protections, ASEAN's diverse economies present a tapestry of approaches. This analysis aims to provide valuable insights for policymakers, scholars, and stakeholders, shedding light on the evolving landscape of labor rights and the future of work in the digital age. This study uses a comparative research design to assess digital platform worker protection in the EU and ASEAN, highlighting differences, similarities, and emerging trends. It involves reviewing official documents and legislative texts from both regions to identify relevant policies and initiatives. This paper found that "digital labor" extends beyond the vast digital landscape, impacting various activities and transforming traditional tasks into digital processes managed by algorithms and automation. Platform workers in regions like the EU and ASEAN face challenges, including extended unpaid waiting times, lack of social security access, unpredictable earnings, and the downside of flexibility. The EU addresses these issues through comprehensive legislative efforts, emphasizing transparency, algorithmic oversight, and clear employment status definitions. In contrast, ASEAN's structure, based on consensus and voluntary cooperation, poses challenges. A binding regional agreement is challenging due to diverse socio-economic and cultural landscapes. Therefore, a non-binding declaration, supported by comprehensive guidelines, may offer a more practical approach. This declaration, symbolizing collective commitment, along with guidelines on best practices, could guide member states in tailoring their national policies to protect platform workers better.